Analisis Hukum Peran Bank Dalam Pembiayaan Proyek Infrastruktur di Indonesia - Yuli Andini Puspitasari; Navyra Berlianny; Mila Sari; Putri Yanti (Pusat Riset dan Inovasi Nasional, 2024)
Infrastructure development in Indonesia can be a factor in the country's progress. because with adequate infrastructure, it can create economic growth and raise the quality of other sectors. Infrastructure development must be encouraged by various parties, one of which is banks. Banking has an important role in infrastructure development, because banks can help the government finance infrastructure projects by purchasing securities and through lending. The method used is normative legal research which focuses on laws and other policies related to the development and financing of infrastructure projects. As a result, in helping the government to finance infrastructure projects, banks provide products in the form of investment credit, syndicated credit, project financing, sharia financing and commercial credit. as the legal basis for financing infrastructure projects in Indonesia, Bank Indonesia issued and ratified PBI No. 23/7/PBI/2021 concerning Implementation of Payment System Infrastructure. With the large role of banks in financing infrastructure projects, it is hoped that they can support national development and encourage better growth in the infrastructure sector in the future. The government and banks need to continue to collaborate well in developing and improving a more effective and sustainable infrastructure project financing system, for the progress of the nation and state.